2012
DOI: 10.1136/thoraxjnl-2012-202678.251
|View full text |Cite
|
Sign up to set email alerts
|

P190 QVA149 Once Daily Provides Significant Improvements in Lung Function Over 1 Year in Patients with COPD: The Enlighten Study: Abstract P190 Table 1

Abstract: Introduction QVA149 is a novel inhaled once-daily dual bronchodilator, containing a fixed-dose combination of the long-acting β 2 -agonist indacaterol and the long-acting muscarinic antagonist NVA237 (glycopyrronium) in development for the treatment of COPD. This study evaluated the long-term effect of QVA149 on lung function in patients with COPD. Methods This was a multicentre, double-blind, parallel group, placebo-controlled study in which patients with moderate-tosevere COPD were randomised (2:1) to receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Mean treatment difference for indacaterol plus glycopyrronium versus salmeterol/fluticasone ranged from 103 mL (trough FEV 1 ) to 155 mL (peak FEV 1 ) [69]. Additionally, the longer-term ENLIGHTEN study reported significant improvements in lung function with the combination versus placebo sustained for 52 weeks, with no evidence of tachyphylaxis [67]. …”
Section: Combination Bronchodilation: Existing Evidence and Ongoing Smentioning
confidence: 99%
“…Mean treatment difference for indacaterol plus glycopyrronium versus salmeterol/fluticasone ranged from 103 mL (trough FEV 1 ) to 155 mL (peak FEV 1 ) [69]. Additionally, the longer-term ENLIGHTEN study reported significant improvements in lung function with the combination versus placebo sustained for 52 weeks, with no evidence of tachyphylaxis [67]. …”
Section: Combination Bronchodilation: Existing Evidence and Ongoing Smentioning
confidence: 99%
“…Na kongresie European Respiratory Society w Wiedniu 2012 roku przedstawiono wyniki pięciu zakończonych badań nowej kombinacji leków LABA/LAMA QVA149 (badania SPARK, SHINE, BRIGHT, ENLIGHTEN, ILLUMINATE) [27][28][29][30][31] u ponad 2 tysięcy chorych. Badania prowadzone były w ramach kompleksowego programu IGNITE, który zakłada łącznie wykonanie 10 badań klinicznych w 42 krajach u 7 tysięcy chorych na umiarkowane i ciężkie POChP.…”
Section: Trudności W Ocenie Odpowiedzi Na Leczenieunclassified